Secondary hyperparathyroidism, weight loss, and longer term mortality in haemodialysis patients: results from the DOPPS. Issue 4 (1st June 2021) - Komaba, Hirotaka; Zhao, Junhui; Yamamoto, Suguru; Nomura, Takanobu; Fuller, Douglas S.; McCullough, Keith P.; Evenepoel, Pieter; Christensson, Anders; Zhao, Xinju; Alrukhaimi, Mona; Al‐Ali, Fadwa; Young, Eric W.; et al.
Abstract: Background: Wasting is a common complication of kidney failure that leads to weight loss and poor outcomes. Recent experimental data identified parathyroid hormone (PTH) as a driver of adipose tissue browning and wasting, but little is known about the relations among secondary hyperparathyroidism, weight loss, and risk of mortality in dialysis patients. Methods: We included 42, 319 chronic in‐centre haemodialysis patients from the Dialysis Outcomes and Practice Patterns Study phases 2–6 (2002–2018). Linear mixed models were used to estimate the association between baseline PTH and percent weight change over 12 months, adjusting for country, demographics, comorbidities, and labs. Accelerated failure time models were used to assess 12 month weight loss as a mediator between baseline high PTH and mortality after 12 months. Results: Baseline PTH was inversely associated with 12 month weight change: 12 month weight loss >5% was observed in 21%, 18%, 18%, 17%, 15%, and 14% of patients for PTH ≥600 pg/mL, 450–600, 300–450, 150–300, 50–150, and <50 pg/mL, respectively. In adjusted analyses, 12 month weight change compared with PTH 150–299 pg/mL was −0.60%, −0.12%, −0.10%, +0.15%, and +0.35% for PTH ≥600, 450–600, 300–450, 50–150, and <50 pg/mL, respectively. This relationship was robust regardless of recent hospitalization and was more pronounced in persons with preserved appetite. During follow‐up after the 12 month weight measure [median, 1.0 (interquartile range, 0.6–1.7) years; 6125 deaths], patients with baseline PTH ≥600 pg/mL had 11% [95% confidence interval (CI), 9–13%] shorter lifespan, and 18% (95% CI, 14–23%) of this effect was mediated through weight loss ≥2.5%. Conclusions: Secondary hyperparathyroidism may be a novel mechanism of wasting, corroborating experimental data, and, among chronic dialysis patients, this pathway may be a mediator between elevated PTH levels and mortality. Future research should determine whether PTH‐lowering therapy can limit weight loss and improve longer term dialysis outcomes.